1989
DOI: 10.1161/01.hyp.14.5.524
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reactivity to the cold pressor test as a predictor of hypertension.

Abstract: Cardiovascular reactivity to stress is hypothesized to be a marker for subsequent neurogenic cardiovascular disease, but few prospective studies of this hypothesis are available. We studied 910 white male medical students who had their blood pressure and pulse rate measured before and during a cold pressor test in the years [1948][1949][1950][1951][1952][1953][1954][1955][1956][1957][1958][1959][1960][1961][1962][1963][1964]. Hypertensive status (requiring drug treatment) was ascertained by annual questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
2
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(180 citation statements)
references
References 42 publications
8
166
2
4
Order By: Relevance
“…[2][3][4][5][6][7][8][9] This supports the reactivity hypothesis, which states that exaggerated physical or psychological responses to stress identify subgroups with increased cardiovascular risk. 10 However, there are some controversies regarding whether this represents a casual relationship.…”
supporting
confidence: 70%
“…[2][3][4][5][6][7][8][9] This supports the reactivity hypothesis, which states that exaggerated physical or psychological responses to stress identify subgroups with increased cardiovascular risk. 10 However, there are some controversies regarding whether this represents a casual relationship.…”
supporting
confidence: 70%
“…In this study, heterogeneity was mostly due to differences in study populations, measures of exposure and outcome, losses and follow-up time. The effect of heterogeneity was partially overcome by the use of random effects models, subgroup analysis, a combination of effect by study and analysis of the impact of Menkes et al a 22 Markovitz et al d 26 Markovitz et al c 26 Markovitz et al b 26 Markovitz et al a 26 Carroll et al b 44 Carroll et al a 44 Matthews et al f 21 Matthews et al e 21 Matthews et al d 21 Matthews et al c 21 Matthews et al b 21 Matthews et al a 21 Borghi et al 43 Steptoe et al h 25 Steptoe et al g 25 Steptoe et al f 25 Steptoe et al e 25 Steptoe et al d 25 Steptoe et al c 25 Steptoe et al b 25 Steptoe Figure 3 Random effects model, odds ratio and 95% confi dence interval for the combined effect by study and the impact of the exclusion of each study.…”
Section: Discussionmentioning
confidence: 99%
“…Data extracted from each article were neperian logarithm of OR and standard error (SE). One study reported the hazard ratio 21 and another reported the relative risk 22 and these measures were converted into OR 23 . When only confidence intervals were available, they were converted into SE 14 .…”
Section: Data Extractionmentioning
confidence: 99%
“…The present study differed in type of stressor (serial-subtraction task) and in the method of measuring vagal activity (heart rate variability via MSD scores). However, despite our use of a stressor known to elicit even greater differences in response between N+PH and N-PH subjects than other stressors, 16,24,28,55 and despite measuring parasympathetic response with a more direct method (MSD), the results of this study paralleled previous studies: we found no differences between the PH groups in parasympathetic response (MSD), at the stages of initial reactivity (P ¼ 0.99, Table 3), subsequent adaptation (P ¼ 0.268, Table 4), or later recovery (P ¼ 0.99, Table 5). Perhaps the decrease in vagal tone seen in essential hypertensive subjects 52,53 develops as a consequence of high blood pressure rather than as a precursor to the disease.…”
Section: Stress Responses and Genetic Risk Of Hypertensionmentioning
confidence: 97%